1972
DOI: 10.1136/gut.13.7.535
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin-containing cells in the small intestine during acute enteritis

Abstract: SUMMARY Jejunal mucosal biopsies were obtained from 13 patients with acute enteritis. Ten patients were examined again after recovery. Quantitative analysis of the findings in immunofluorescence microscopy showed a significant increase of IgA-and IgM-containing cells during acute enteritis. After recovery the number of immunoglobulin-containing cells and their distribution within the different immunoglobulin classes were within normal limits.The lamina propria of the gastrointestinal tract is richly endowed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1974
1974
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 11 publications
0
5
1
Order By: Relevance
“…There were increases in the numbers of IgM-and IgA-containing cells; however, these increases were less marked than in the malabsorption syndrome with cow's milk protein intolerance. Similar increases in numbers of immunoglobulineontaining cells have been reported in coeliac disease (13) and, for example, in viral gastroenteritis (17), and such increases are thus a common response to various antigens. According to this study, immune r-eactions involving increases in these cells are a common feature in food allergy presenting as eczema; in contrast to the malabsorption syndrome with cow's milk pr-otein intolerance and coeliac disease with similar incr-eases, most patients in this study have normal morphology of the intestine.…”
Section: Disgussioncontrasting
confidence: 40%
“…There were increases in the numbers of IgM-and IgA-containing cells; however, these increases were less marked than in the malabsorption syndrome with cow's milk protein intolerance. Similar increases in numbers of immunoglobulineontaining cells have been reported in coeliac disease (13) and, for example, in viral gastroenteritis (17), and such increases are thus a common response to various antigens. According to this study, immune r-eactions involving increases in these cells are a common feature in food allergy presenting as eczema; in contrast to the malabsorption syndrome with cow's milk pr-otein intolerance and coeliac disease with similar incr-eases, most patients in this study have normal morphology of the intestine.…”
Section: Disgussioncontrasting
confidence: 40%
“…These include the infections (S0ltoft and Seberg, 1972;Davidson et al, 1975), pernicious anaemia (Odgers and Wangel, 1968), chronic gastritis unassociated with pernicious anaemia, coeliac disease (Douglas et al, 1970), tropical and temperate sprue (Swanson and Thomassen, 1965;Drummond and Montgomery, 1970), ulcerative colitis and Crohn's disease (Skinner and Whitehead, 1974), and alpha chain disease (Manousos et al, 1974). There is sufficient evidence from these studies that further investigation using the more elaborate and accurate methods outlined-above will yield much more valuable data.…”
Section: Quantitative Methodsmentioning
confidence: 99%
“…This finding seems to be by far the most important immunological characteristic of the small intestine in celiac disease. It is a particularly important observation in view of the fact that in no other disease (acute enteritis [22], cirrhosis of the liver with diarrhoea [5], Whipple's disease [7], viral hepatitis [23]) has an isolated increase in the IgM cell concentration in the jejunum ever been demonstrated. Furthermore, an IgM cell increase has not been found in other diseases with an immunological etiology (Crohn's disease, ulcerative colitis [21]).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the immunoglobulins are mostly found in the lymphocytes and plasma cells of the jejunal mucosa and it has been demonstrated that the number of cells containing the different types of immunoglobulins can vary under different pathophysiological conditions [2,3,5,7,16,[21][22][23][24], But no correlation has yet been demonstrated between the immunoglobulin content of the jejunal mucosa and the immunoglobulin in the intestinal secretion and in the blood [1,[11][12][13]20], In this context the work of Soltoft and Weeke [24], Douglas et al [7], and Pettingale [16] in adult celiac patients is particularly important.…”
Section: Abstract the Density Of The Three Principal Immunoglobulin-mentioning
confidence: 99%